Energy Condition of Subsistence‐Harvested Fishes in Arctic Coastal Lagoons. Issue 6 (12th November 2021) - Fraley, Kevin M.; Robards, Martin D.; Vollenweider, Johanna; Whiting, Alex; Jones, Tahzay; Rogers, Matthew C.
Abstract: In Arctic Alaska, Indigenous and rural residents depend on wild‐harvested foods for sustenance and the subsistence lifestyle is integral to their culture. Marine and diadromous fishes, which often occupy coastal lagoon habitats, are relied upon for subsistence harvest, particularly Pacific salmon, whitefishes (Coregoninae), cods (Gadidae), and flounder species (Pleuronectidae). However, little research has been conducted that assesses the energetic condition of these fishes, which are harvested by the tens of thousands annually. The effects of accelerating climate change and human development on the metabolic rates, diet, body condition, and energy density of fish is of great concern because these effects will, in turn, affect the people who depend on these species for food security. Consequently, we characterized energy density and percentage of lipid, water, and protein content of 10 fish species in four coastal lagoons within Cape Krusenstern National Monument, Alaska. We found that whitefishes, particularly Bering Cisco Coregonus laurettae and Least Cisco C. sardinella exhibited the highest energy density, percentage of lipid, and percentage of protein content, significantly greater than that of marine cod and flounder species, Fourhourn Sculpin Myoxocephalus quadricornis, freshwater Pond Smelt Hypomesus olidus, and values from other regional species that have been in published literature. Additionally, when the relative mean abundance and body weight of each species was taken into account, total energy value by availability in the lagoons was highest for whitefishes when compared with marine taxa and the freshwater Pond Smelt. Given the impending effects of climate change and coastal construction in the region, it will be important to monitor the energy condition of lagoon fishes to ensure their quality and availability for subsistence harvesters.